2022
DOI: 10.1017/pab.2022.28
|View full text |Cite
|
Sign up to set email alerts
|

Paleohistological inferences of thermometabolic regimes in Notosuchia (Pseudosuchia: Crocodylomorpha) revisited

Abstract: Notosuchia is a group of mostly terrestrial crocodyliforms. The presence of a prominent crest overhanging the acetabulum, slender straight-shafted long bones with muscular insertions close to the joints, and a stable knee joint suggests that they had an erect posture. This stance has been proposed to be linked to endothermy, because it is present in mammals and birds and contributes to the efficiency of their respiratory systems. However, a bone paleohistological study unexpectedly suggested that Notosuchia we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 73 publications
2
11
0
Order By: Relevance
“…Their probable ectothermic metabolism (Cubo et al . 2020, 2022) could have strongly restricted their possible dispersal to higher latitude and habitats. Lower latitude and habitats seem to be a limiting constraint too, maybe because the rainforest of tropical climates may have been problematic for terrestrial cursorial crocodyliforms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their probable ectothermic metabolism (Cubo et al . 2020, 2022) could have strongly restricted their possible dispersal to higher latitude and habitats. Lower latitude and habitats seem to be a limiting constraint too, maybe because the rainforest of tropical climates may have been problematic for terrestrial cursorial crocodyliforms.…”
Section: Discussionmentioning
confidence: 99%
“…Notosuchians were probably ectothermic (Cubo et al . 2020, 2022). Almost all of them were adapted to a terrestrial environment (Wu & Sues 1996; Gomani 1997; Pol 2005; Turner 2006; Sereno & Larsson 2009; Nascimento & Zaher 2010; Riff & Kellner 2011; Godoy et al .…”
mentioning
confidence: 99%
“…This kind of scenario probably occurred in the loss of endothermy or, at least, tachymetabolism, in the crocodilian clade. 12 , 15 , 32 , 43 …”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the size of the erythrocytes and HMC is thus not always exact, despite the statistical relationship still being significant. 32 Moreover, Starck and Chinsamy 34 demonstrated that the size of vascular canals can vary accordingly to the availability of food during osteogenesis: less available food leads to smaller vascular canals and, consequently, to an overestimation of . Then, an ectothermic taxon can be wrongly associated with endothermy because of food limitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation